Singapore's high wage policy revisited - Lim, Chong Yah (2022)
The author, now aged 90, reflects on the then highly iconoclastic National Wages Council (NWC) recommendation of a 20% yearly gross wage increase guideline for three years, 1979-1981. He emphasizes the important differences between the negotiable and the non-negotiable recommended wage increases. He also emphasizes the important difference between a pure percentage wage increase and a quantum plus percentage wage increase formula particularly in the integral economic restructuring program. The compulsory payments consisting of the important Central Provident Fund (CPF) increases and the new Restructuring Skills Development Fund (SDF) Levy. The increase in the compulsory CPF led to the formation of the Sovereign Wealth Fund-The Government Investment Corporation (GIC). The restructuring led to the creation of the SDF. The SDF was used to promote labor productivity through the then equally iconoclastic substitution of capital for labor programs. The end result of the restructuring policy was to minimize demand-pull inflationary pressures, increase the gross wages of low-wage and medium-wage workers and increase real Gross Domestic Product (GDP) growth rates, accompanied by an important fall in the Gini Coefficient of income inequality. The anti-cyclical preparedness of the high-wage economic restructuring program is also emphasized and the idea of discussing the high-wage policy in isolation is debunked.